2022
DOI: 10.3389/fpsyt.2022.957951
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the utilization, processes, and outcomes of inpatient mental healthcare during the first three waves of the COVID-19 pandemic in the federal state of North Rhine-Westphalia, Germany

Abstract: BackgroundDuring the first phase of the Coronavirus-19 disorder (COVID-19) pandemic in the spring of 2020, utilization of inpatient mental healthcare was significantly reduced. We now report on a long-term observational study of inpatient mental healthcare in a large psychiatric hospital association in North Rhine-Westphalia, Germany, covering the second and third pandemic waves of autumn and winter 2020 followed up until June 2021.ObjectivesAnalysis of the changes of inpatient and day patient mental healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…45,46 The annual trend of admissions divided between VHs and IHs shows a progressive sharp decrease in VHs admissions, concurrent with the pandemic, while the number of IHs admissions remained relatively stable over time, surpassing the number of VHs admissions in absolute terms by the year 2022. This result clearly highlights that, despite the emergency situation, there was a portion of individuals whose admission was necessary and urgent due to acute and severe conditions, and this is in line with national and international studies, 42,[47][48][49][50] which reported a similar trend during pandemic with an increase in involuntary hospitalizations and coercive measures in Psychiatry. In accordance with most authors, we can hypothesize that, during pandemic, reduced availability of outpatient service activities and, at the same time, stressful conditions of isolation as well as reduced treatment of non-COVID-19 related disorders could have…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…45,46 The annual trend of admissions divided between VHs and IHs shows a progressive sharp decrease in VHs admissions, concurrent with the pandemic, while the number of IHs admissions remained relatively stable over time, surpassing the number of VHs admissions in absolute terms by the year 2022. This result clearly highlights that, despite the emergency situation, there was a portion of individuals whose admission was necessary and urgent due to acute and severe conditions, and this is in line with national and international studies, 42,[47][48][49][50] which reported a similar trend during pandemic with an increase in involuntary hospitalizations and coercive measures in Psychiatry. In accordance with most authors, we can hypothesize that, during pandemic, reduced availability of outpatient service activities and, at the same time, stressful conditions of isolation as well as reduced treatment of non-COVID-19 related disorders could have…”
Section: Discussionsupporting
confidence: 87%
“… 50 These results were confirmed by another study, which reported that while voluntary cases decreased considerably during the pandemic, involuntary cases increased slightly, indicating a deterioration in treatment quality during the pandemic. 48 Another study further confirmed these results during the COVID-19 pandemic, 49 suggesting an overall increased severity of mental disorders during the pandemic, due to deferrals of admissions or reduction of mental healthcare services interventions. This unexpected result underlines the need for regular and careful monitoring of the most serious psychiatric conditions, especially in the outpatient setting, particularly for preventing non-adherence to treatment, the main cause of involuntary hospitalization.…”
Section: Discussionmentioning
confidence: 76%
“…In Germany, Flammer et al (2022) reported an increase in the percentage of involuntary admissions and the utilization of seclusions and restraints in 2020. Zielasek et al (2022) studied the utilization of inpatient mental health care in Germany during the first waves of the COVID-19 pandemic. They reported increased use of seclusions and restraints and increased admission of patients with psychotic symptoms during that period.…”
Section: Discussionmentioning
confidence: 99%
“…Many facilities and public services (e.g., shelters, group homes, schools, social services) had to shut down or limit access, making patient discharges more complex and increasing patients' length of hospital stay (LOS). Recent studies reported increased involuntary admissions and use of coercive measures, such as restraints and seclusion, during the pandemic (Flammer et al, 2022;Zielasek et al, 2022).…”
Section: Disrupted Access To Health Care and Alteration Of Behavioral...mentioning
confidence: 99%
“…Consistent with previous reports, this study highlights the impact of COVID-related social distancing on the incidence of inpatient aggression. Studies have shown both increased and decreased rates of inpatient aggression during the COVID-19 pandemic [27][28][29][30][31]. One reason for this heterogeneity of results may be that many studies did not adjust for hospital bed occupancy in their analysis.…”
Section: Discussionmentioning
confidence: 99%